2023
DOI: 10.3389/fnut.2023.1118229
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of resistant starch types on glycemic response in individuals with type 2 diabetes or prediabetes: A systematic review and meta-analysis

Abstract: BackgroundType 2 diabetes (T2D) diagnoses are predicted to reach 643 million by 2030, increasing incidences of cardiovascular disease and other comorbidities. Rapidly digestible starch elevates postprandial glycemia and impinges glycemic homeostasis, elevating the risk of developing T2D. Starch can escape digestion by endogenous enzymes in the small intestine when protected by intact plant cell walls (resistant starch type 1), when there is a high concentration of amylose (resistant starch type 2) and when the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 84 publications
0
13
0
1
Order By: Relevance
“…Nonetheless, Pugh et al, in their subgroup analyses, highlighted that significant effects on glycemic response were primarily observed with RS1 and RS2 but not with RS3. This observation can be attributed to the fact that RS1 and RS2 received more extensive research attention across the scientific literature, whereas the analysis of RS3 was based on only two studies ( 64 ). A limited number of clinical trials also focused on RS4.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nonetheless, Pugh et al, in their subgroup analyses, highlighted that significant effects on glycemic response were primarily observed with RS1 and RS2 but not with RS3. This observation can be attributed to the fact that RS1 and RS2 received more extensive research attention across the scientific literature, whereas the analysis of RS3 was based on only two studies ( 64 ). A limited number of clinical trials also focused on RS4.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the benefits of the different types of RS are likely exerted through different pathways ( 64 ), as demonstrated by the varying microbiota responses to different types of RS. For instance, after 12 weeks of consuming 12 g of RS4 daily, a significant decrease in bile acid in stools were reported compared to control ( 79 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the results of a meta-analysis reported that resistant starch supplementation is associated with an improvement in blood glucose, insulinemia, insulin sensitivity, and resistance, especially in patients with diabetes and overweight or obesity [ 160 ]. More specifically, type 1 and type 2 resistant starches have been associated with improved post-prandial blood glucose, and in addition, type 2 resistant starch has been associated with improved post-prandial insulin response and fasting blood glucose [ 162 ]. The use of type 3 resistant starch for 3 to 11 weeks resulted in a reduction in fasting blood glucose, triglycerides, and total cholesterol in a diabetic mice model [ 163 ].…”
Section: Effects Of Macronutrients On T2dm and Gut Microbiotamentioning
confidence: 99%